Carrier frequency of autosomal recessive disorders (BC, BLAD, FXID and CVM) in Holstein cows in Jalisco, Mexico - Virgen-Méndez,Abraham (2019)
ABSTRACT: The hereditary autosomal recessive disorders bovine citrullinemia (BC), bovine leukocyte adhesion deficiency (BLAD), factor XI deficiency (FXID), and complex vertebral malformation (CVM) have affected dairy cattle breeding significantly around the world. This study examined the carrier frequency of BC, BLAD, FXID, and CVM autosomal recessive disorders in Bos taurus Holstein cows bred in the Altos Norte region of the state of Jalisco, Mexico. We extracted DNA from 408 random samples of peripheral blood, and then used polymerase chain reaction (PCR) to identify insertion mutations for FXID, and PCR with restriction fragment length polymorphism (PCR-RFLP) for CVM, BC and BLAD. We visualized the PCR products using agarose gel electrophoresis stained with GelRed®. We found that 100% of wild-type (N/N) allele homozygous animals for genes CD18, ASS, and FXI were free of the mutations for BLAD, BC and FXID respectively. For gene SLC35A3 we estimated total carrier frequency of 10.3% and allele frequency of 5%.